Management Scientists Are Human - Hofstede, Geert (Management Science, 1994)
The culture of the national environment in which an organization operates affects the management process through the collective mental programming of its members, its managers, and the management scientists who offer their theories. Four dimensions of national culture differences have been found. Among other things, they affect the implicit models in people's minds of what the act of organizing means. Among the pioneers in management science around 1900, differences along these dimensions are already noticeable. A fifth dimension was added when the research instrument used was designed exclusively by Chinese scholars, and it provides a cultural explanation for the economic success of East Asian countries in the past quarter century. At the same time, it highlights the influence of the culture of the management scientist on the research questions and the resulting theories.